2014
DOI: 10.3109/00016489.2013.871747
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of p53 expression in negative surgical margins of early glottic carcinoma in the prediction of local recurrences

Abstract: Median p53 in the primary tumor was 55% (interquartile range (IQR) = 67) and 5% (IQR = 71) in groups 1 and 2, respectively (p = 0.178). Median p53 in the surgical margin was 11% (IQR = 13) and 2% (IQR = 2) in groups 1 and 2, respectively (p = 0.001). In the logistic regression analysis only surgical margin p53 value was significant in the prediction of recurrences (odds ratio (OR) = 1.68, 95% CI = 1.1-2.6, p = 0.017). Receiver operating characteristic (ROC) curve analysis demonstrated that the area under the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…27 Ozturk et al proposed that, in the surgical treatment of early glottic carcinoma, overexpression of P53 was more valuable for predicting recurrence and prognosis in the incisional margin tissue than in the primary tumor tissue. 28 P27 is a member of the cyclin-dependent kinase inhibitors family, which plays a negative regulatory role in the cell cycle, preventing the cell cycle from entering the S phase, thereby inhibiting cell proliferation. 29 After detecting the expression of P27 protein in laryngeal squamous cell carcinoma, researchers concluded that the inactivation of P27 in resection margin tissues was closely related to local recurrence of laryngeal cancer.…”
Section: Tumor Suppressor Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…27 Ozturk et al proposed that, in the surgical treatment of early glottic carcinoma, overexpression of P53 was more valuable for predicting recurrence and prognosis in the incisional margin tissue than in the primary tumor tissue. 28 P27 is a member of the cyclin-dependent kinase inhibitors family, which plays a negative regulatory role in the cell cycle, preventing the cell cycle from entering the S phase, thereby inhibiting cell proliferation. 29 After detecting the expression of P27 protein in laryngeal squamous cell carcinoma, researchers concluded that the inactivation of P27 in resection margin tissues was closely related to local recurrence of laryngeal cancer.…”
Section: Tumor Suppressor Genesmentioning
confidence: 99%
“…27 Ozturk et al proposed that, in the surgical treatment of early glottic carcinoma, overexpression of P53 was more valuable for predicting recurrence and prognosis in the incisional margin tissue than in the primary tumor tissue. 28…”
Section: Relationship Between Common Molecular Biomarkers and Prognosismentioning
confidence: 99%
“…The results of the immunohistochemical staining were evaluated by an anatomo-pathologist doctor. As described in previous studies, 5% of the cutoff for survivin and p53 expression, 15,16 1% for p16 expression 17 and 6% for IGF-1R expression 18 were considered. The survivin and p53 immunostaining was scored as follows: score 0: <5%; score 1: 5% to 25%; score 2: 26% to 50%; score 3: >50%.…”
Section: Evaluation Of Immunostainingmentioning
confidence: 99%